(untitled) (Journal of Asian Development Studies, 2023)
Early marriage violates human rights as it deprives the performer of fully compromising on the individuality, career, education, and self of the one performing it. The study explored the determinants and impacts of early marriage on women’s empowerment. Italso tested the relationship between early marriage and women’s empowerment. Early marriage impact on women negatively and positively. Some reasons that affect women’s lives badly. Poverty, lack of education, and exchange marriage is the main reason for early marriage. Parents early married their daughter because they could not afford her expenses. Early marriage also creates better communication and love between husband and wife. The research was conducted in District Sudhnoti, Tehsil Balouch, Azad Jammu Kashmir. The quantitative research design was married women, wherein 120 married females were interviewed through a questionnaire schedule. The sample was selected through the snowball sample technique. Later on, the data was codified and then analyzed through SPSS. The studies exposed that poor legislation, cultural support, and supposed value were some of the essential causes behind the menace. Furthermore, it contributed to their lack of education, poverty, illiteracy, over-population, family clashes, domestic violence, and patriarchal structure.